2019
DOI: 10.1111/ijfs.14446
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid method for codfish identification in processed fish products based on SYBR Green real‐time PCR

Abstract: Summary Using species outside the order Gadiformes to prepare codfish products has been widely revealed as a new type of fraud in China, highlighting the necessity to establish proper methods for codfish species identification. This work aimed to develop a new SYBR Green real‐time PCR assay for the detection of codfish ingredient (mainly the eight Gadiformes species, Gadus morhua, Gadus macrocephalus, Theragra chalcogramma, Pollachius virens, Melanogrammus aeglefinus, Merluccius merluccius, Merluccius australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Compared with morphology-based identification methods, DNA-based analysis is useful for identification of fish species [11][12][13]. This method is preferable because DNA is more stable under high temperatures and pressure conditions compared with protein.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with morphology-based identification methods, DNA-based analysis is useful for identification of fish species [11][12][13]. This method is preferable because DNA is more stable under high temperatures and pressure conditions compared with protein.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, highly processed samples (thermal or high pressure treated) may exhibit low DNA integrity; as such, it is important that DNA-based assays can detect small fragment sizes (<200 bp). Many of the conventional PCR assays reviewed amplified DNA target regions <200 bp (Acar et al, 2017;Hellberg et al, 2010;Kang, 2019;Laknerová et al, 2014;Lin & Hwang, 2008a;Xiong et al, 2020). Xiong et al (2020) assessed the sensitivity of conventional PCR.…”
Section: 24mentioning
confidence: 99%
“…Many of the conventional PCR assays reviewed amplified DNA target regions <200 bp (Acar et al, 2017;Hellberg et al, 2010;Kang, 2019;Laknerová et al, 2014;Lin & Hwang, 2008a;Xiong et al, 2020). Xiong et al (2020) assessed the sensitivity of conventional PCR. In this study, the species-specific band of cod samples was reported to be more sensitive than SYBR Green real-time PCR but less sensitive than TaqMan probe real-time PCR.…”
Section: 24mentioning
confidence: 99%
“…In addition, the barcoding methodology which is reliable, accurate and reproducible, has been improved to make it time and cost-effective and then useful for routine screening by industry and for food forensics investigations. Implementation has been obtained by coupling the barcoding with classic and new generation methodologies, such as the Random Fragment Length Polymorphisms (RFLP), High Resolution Melting Analysis (HRMA) and species-specific Real Time Polymerase Chain Reaction (PCR) [ 39 , 40 , 41 ]. For several years, the RFLP methodology based on the digestion of restriction enzymes applied to the COI sequences, renamed COIBar-RFLP [ 42 ] has been successfully used for species authentication in processed seafood [ 11 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%